Perceptions of Reportable Disease Lists by State Officials in the United States. Issue 1 (18th March 2013) - Allen, Heather; Katz, Rebecca
Abstract The purpose of this research was to assess the perceptions of state officials about the importance of reportable disease lists in encouraging disease reporting. An electronic survey was sent to state veterinarian, state public health veterinarians, and state epidemiologists inquiring about their perceptions (based on official responsibilities) of the importance of reportable disease lists. MS Excel was used to calculate frequency counts and proportions; chi‐square statistics were calculated to assess differences between categories of respondents. The response rate was 40 percent for state veterinarians, 44 percent for state public health veterinarians, and 78 percent for state epidemiologists. State officials perceive (90 percent) that reportable disease lists are an effective policy mechanism to encourage disease reporting, though 43 percent believe underreporting of reportable diseases is a problem, and 43 percent believe the problem of underreporting exists, but varies by disease. Fifty‐five percent of respondents believe it is important that reportable disease lists have legal enforcement mechanisms associated with them, though 31 percent believe they would be too difficult to enforce. Responses across the three categories of officials were generally consistent. Electronic reporting and additional education were suggested to improve disease reporting. Because notifiable disease reporting remains an important part of disease detection, further improvements are needed to encourage infectious disease reporting. These results present evidence that state officials from both animal and health sectors perceive that education and electronic reporting would be more effective in improving reporting completeness than regulatory penalties.